PENERAPAN PROBLEM BASED LEARNING PADA KOMPETENSI RIAS WAJAH FOTO BERWARNA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI JURUSAN KECANTIKAN DI SMK NEGERI 8 SURABAYA - Syabana, Tsania Rachmani; Nia Kusstianti; Novia Restu Windayani; Sri Dwiyanti (Jurnal Tata Rias, 2025)
Learning activities play an important role in student learning outcomes, especially in vocational high schools (SMK) that require skill acquisition. Color photography makeup competency in the beauty care major requires an understanding of anatomy theory and practical skills. The PBL model was chosen because it has the potential to improve students’ comprehension, group work, and interpersonal skills. The objective of this research is to identify the implementation of PBL constructs, student knowledge acqusition outcomes, and learner feedback. This research employed a pilot experimental design approach with a single-group pre-posttest design. The research tools consisted of observation sheets, cognitive and psychomotor tests, and questionnaires. The results showed that the implementation of PBL constructs was classified as very good with an average score of 3.84. Cognitive learning outcomes significantly increased from 65 to 84 points, and were classified as optimal. Psychomotor learning outcomes were classified as very good with 21 students in the very good category and 3 students in the good category. The response rate of students was 91%, which was evaluated as very good. In conclusion, the introduction of PBL can effectively optimize learning outcomes and students’ learning enthusiasm in the color photography makeup learning process